Writing Spaces Readings on Writing Vol. II - Lowe, Charlie; Zemliansky, Pavel; Open Textbook Library (Open Textbook Library, 2011)
Volumes in Writing Spaces: Readings on Writing offer multiple perspectives on a wide-range of topics about writing. In each chapter, authors present their unique views, insights, and strategies for writing by addressing the undergraduate reader directly. Drawing on their own experiences, these teachers-as-writers invite students to join in the larger conversation about the craft of writing. Consequently, each essay functions as a standalone text that can easily complement other selected readings in writing or writing-intensive courses across the disciplines at any level. Volume 2 continues the tradition of the previous volume with topics, such as the rhetorical situation, collaboration, documentation styles, weblogs, invention, writing assignment interpretation, reading critically, information literacy, ethnography, interviewing, argument, document design, and source integration.
Ten Ways To Think About Writing: Metaphoric Musings for College Writing Students -- Composition as a Write of Passage -- Critical Thinking in College Writing: From the Personal to the Academic -- Looking for Trouble: Finding Your Way into a Writing Assignment -- How to Read Like a Writer -- Murder! (Rhetorically Speaking) -- The Complexity of Simplicity: Invention Potentials for Writing Students -- Writing "Eyeball To Eyeball": Building A Successful Collaboration -- On the Other Hand: The Role of Antithetical Writing in First Year Composition Courses -- Introduction to Primary Research: Observations, Surveys, and Interviews -- Putting Ethnographic Writing in Context -- Walk, Talk, Cook, Eat: A Guide to Using Sources -- Reading Games: Strategies for Reading Scholarly Sources -- Googlepedia: Turning Information Behaviors into Research Skills -- Annoying Ways People Use Sources -- Everything Changes, or Why MLA Isn't (Always) Right -- Storytelling, Narration, and the "Who I Am" Story -- The Sixth Paragraph: A Re-Vision of the Essay -- Why Blog? Searching for Writing on the Web -- A Student's Guide to Collaborative Writing Technologies -- Beyond Black on White: Document Design and Formatting in the Writing Classroom
In English.
Description based on online resource
Keywords: Humanities -- Textbooks; Rhetoric -- Textbooks